Unveiling the Halal Food Internationalization Literature: Trends and Prospects for Future Study Direction - Hani Khairo Amalia; Aisyah As-Salafiyah; Ari Prasetyo; Amalia Masruroh (ITB AAS INDONESIA Surakarta, 2025)
The halal industry is a large and rapidly growing market that encompasses various sectors. This review of literature is motivated by the growing demand for halal products, the importance of trade among Muslim-majority nations, and the need for a deeper understanding of how companies deal with competitive barriers when venturing into new markets. Bibliometric analysis used to identify key publications, authors, and keywords, as well as to track trends and patterns over time. The findings of this study can inform businesses, policymakers, and industry stakeholders about effective approaches to internationalizing halal food businesses and contribute to the sustainable growth of the halal food industry. Moreover, identifying several key research trends and gaps can provide insights for future researchers, especially in unexplored areas within the study of the internationalization of halal food.